Gothic Travel through Haunted Landscapes : Climates of Fear - Armitt, Lucie (Anthem studies in gothic literature (Anthem Press), 2023)
This book argues that travel in Gothic literature offers a unique and transformative perspective on recurring cultural preoccupations with fear, unknown landscapes, environmental change, surveillance, and the foreign.